1986
DOI: 10.1002/jcu.1870140608
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of hemorrhagic ovarian cysts

Abstract: The sonographic appearance of hemorrhagic ovarian cysts (HOC) has received little attention aside from a recent report in adolescent girls. We reviewed the sonographic findings in 14 adults with 15 pathologically proven HOC to see whether there were any consistent sonographic findings that, along with the clinical history, might make possible the diagnosis. The majority (93%) of patients presented with the abrupt onset of lower abdominal or pelvic pain, and each, when clinically appropriate, had a negative ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
0
11
1
1
Order By: Relevance
“…Despite contentions that the offending cyst is often not found [2], a vestige of the ruptured cyst was seen in most patients in our study. If not seen at transabdominal ultrasound, an ovarian cyst or its remnant should be sought at endovaginal sonography in a woman of childbearing age who presents with a large hemoperitoneum.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Despite contentions that the offending cyst is often not found [2], a vestige of the ruptured cyst was seen in most patients in our study. If not seen at transabdominal ultrasound, an ovarian cyst or its remnant should be sought at endovaginal sonography in a woman of childbearing age who presents with a large hemoperitoneum.…”
Section: Discussioncontrasting
confidence: 59%
“…The etiology for cyst rupture is not known, although it has been suggested that the increased vascularity of the ovary in the luteal phase may predispose to rupture of a corpus luteal cyst [6]. Although the sonographic appearance of the contained hemorrhage within an ovarian cyst has been well described [1][2][3][4][5], the imaging findings associated with cyst rupture and hemorrhage have not been similarly described in the literature. Consequently, patients with a ruptured ovarian cyst are frequently misdiagnosed with unrelated gynecologic, urologic, or gastrointestinal disorders both before and after imaging evaluation [6,7].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…are usually diagnosed on ultrasound (US); the follow-up examination, showing the disappearance of the lesion, is usually sufficient to confirm the diagnosis (1)(2)(3)(4). Magnetic resonance (MR) imaging is rarely performed, because it is only done in case of an associated pathology, suspected complication, or an atypical aspect on US.…”
Section: Ovarian Functional Hemorrhagic Cysts (Fhc)mentioning
confidence: 99%